Bisphenols in the pathology of reproduction - Ješeta, M; Crha, T; Žáková, J; Ventruba, P (Ceska gynekologie, 2019)
OBJECTIVE: Bisphenols are one of the most widespread endocrine disruptors that the population of west world countries is exposed to. Objective of this study is to summarize information about influence of bisphenols on reproduction health. DESIGN: Review article, Setting: Department of Obstetrics and Gynecology, Faculty of Medicine, Masaryk University and University Hospital Brno. METHODS: PubMed was searched for articles in English indexed bisphenol and reproduction up to October 2018. RESULTS: Increased levels of bisphenol A and S have been proven in body fluids and tissues. Bisphenol molecules have effect similar to estrogens therefore they influence hormonal regulation and activity of estrogen receptors. Their negative influence on oocyte maturation, spermatogenesis and development of reproductive system has been shown. Bisphenol S, which has replaced bisphenol A, has comparable negative effects on reproduction. CONCLUSION: Bisphenols are widespread endocrine disruptors that could cause severe fertility disorders of men and women.
Keywords: Phenols; Benzhydryl Compounds; Reproduction; těhotenství; benzhydrylové sloučeniny; mužské pohlaví; nesteroidní estrogeny; endocrine disruptor; reproduction; endokrinní disruptory; oocyte; fenoly; bisphenol; Oocytes; ženské pohlaví; Endocrine Disruptors; oocyty; Humans; Pregnancy; Estrogens, Non-Steroidal; Spermatogenesis; spermatozoa; rozmnožování; Female; spermatogeneze; lidé; Male